Constructive alignment of a research-informed teaching activity within an undergraduate diagnostic radiography curriculum: A reflection. Issue 1 (September 2017) - Higgins, R.; Hogg, P.; Robinson, L.
Abstract: Aim: To evaluate the learning experience of a level 5 (year 2) student cohort within a research-informed teaching (RiT) activity and to map findings against learning outcomes and level descriptors using constructive alignment. Method: An online questionnaire was used to explore the level 5 student experience of a Research-informed Teaching (RiT) activity. Responses were retrospectively mapped against Framework for Higher Education Qualifications (FHEQ) level descriptors for level 5 using constructive alignment. Results and Discussion: Thirty one out of 46 level 5 students completed the questionnaire (67% response rate). Analysis of the questionnaire supported the integration of this RiT activity within the curriculum in terms of learning and research skill development by students. However, it was identified that this activity could be revised further to better align with level 5 descriptors and incorporate additional higher level cognitive processes. Conclusion: Learning outcomes for this RiT activity were constructively aligned with FHEQ level 5 descriptors. Recommendations are provided on how these could be further refined to ensure students undertake a more critical approach to the application of theory into practice. Discussion also considers how this process could be used to develop a similar RiT activity at level 6 (year 3). Highlights: Constructive alignment helped to ensure that the learning outcomes were appropriately aligned with level 5 descriptors. Reflection identified outcomes that required further improvement to focus on higher-order thinking and application skills. This article also illustrates how this process could be used to develop a level 6 RiT activity.